Clinical and radiological analysis of the effects of three different lumbar transpedicular dynamic stabilization system on disc degeneration and regeneration - Karadag, Mehmet Kursat; Akgun, Mehmet Yigit; Basak, Ahmet Tulgar; Ates, Ozkan; Tepebasili, Mehmet Ali; Gunerbuyuk, Caner; Oktenoglu, Tunc; Sasani, Mehdi; Ozer, Ali Fahir (Frontiers in Surgery, 2023)
Objective This study aims to assess the clinical outcomes of three transpedicular dynamic systems in treating degenerative disc disease and evaluate their impact on both clinical and radiological aspects of the operated and adjacent segments. Materials and methods A total of 111 patients who underwent posterior transpedicular short-segment dynamic system procedures for treatment of degenerative disc disease were included. The patients were categorized into three groups, namely, Group 1 (Dynesys system, n = 38), Group 2 (Safinaz screw + PEEK rod, n = 37), and Group 3 (Safinaz screw + titanium rod, n = 36). Disc regeneration in the operated segment and disc degeneration in the operated, upper, and lower adjacent segments were assessed using the Pfirrmann Classification. Results Postoperatively, a statistically significant difference was observed in visual analog scale and Oswestry Disability Index scores (p < 0.001). However, no statistically significant difference was seen in disc degeneration/regeneration and degeneration scores of the upper and lower adjacent segments between the preoperative and postoperative groups (p = 0.763, p = 0.518, p = 0.201). Notably, a positive effect on disc regeneration at the operated level (32.4%) was observed. No significant differences were found between the groups in terms of operation rates, screw loosening, and screw breakage after adjacent segment disease (p > 0.05). Conclusion In patients without advanced degeneration, all three dynamic systems demonstrated the ability to prevent degeneration in the adjacent and operated segments while promoting regeneration in the operated segment. Beyond inhibiting abnormal movement in painful segments, maintaining physiological motion and providing axial distraction in the operated segment emerged as key mechanisms supporting regeneration.